THE DYNAMICS OF EU-RUSSIA ENERGY DIPLOMACY AFTER THE UKRAINE WAR 2022-2024 - Pratita, Chika Kirana Budi; Pratama, Rendy Putra (Journal of Social Political Sciences, 2025)
The ongoing conflict in Ukraine has fundamentally altered the landscape of energy diplomacy between the European Union (EU) and the Russian Federation, resulting in a profound reconfiguration of global energy geopolitics. In response to the crisis, the EU has initiated a strategic decoupling from Russian energy dependence, marked by a comprehensive recalibration of its energy policy. The period from 2022 to 2024 is characterized by the implementation of disruptive measures, including economic sanctions, diversification of energy supply sources, and an accelerated transition toward renewable energy systems. This study employs a qualitative comparative methodology, incorporating the analysis of official policy documents and energy trade data, to examine the evolving energy relationship between the EU and Russia. The findings reveal that the war has catalyzed a significant shift in the EU's energy import patterns, particularly in reducing reliance on Russian gas and oil. The EU has actively engaged in forging new energy partnerships with alternative suppliers such as Azerbaijan, Qatar, and the United States, while simultaneously enhancing investments in green energy infrastructure. Concurrently, Russia has reoriented its energy export strategy toward Asian markets, reflecting a broader geopolitical realignment. The study concludes that the Ukraine conflict has accelerated the fragmentation of traditional energy interdependence between the EU and Russia, fostering the emergence of new diplomatic alignments and reinforcing the strategic importance of energy autonomy and diversification in contemporary international relations.